2019
DOI: 10.1016/j.jcae.2019.100162
|View full text |Cite
|
Sign up to set email alerts
|

Informal institutions and managers’ earnings management choices: Evidence from IFRS-adopting countries

Abstract: In this study, we investigate the role of informal institutions (religiosity and culture) in determining managers' choices of earnings management methods (accruals vs. real activities), after controlling for formal institutions (investor protection, enforcement quality and equity market development). Using an ethical perspective, we find that managers tend to choose an earnings management strategy that meets the prevailing social (informal) norms of the environment where the firm is headquartered. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 80 publications
1
23
0
4
Order By: Relevance
“…Newest studies attempt to investigate qualitative issues such as the religious and cultural aspects associated with accounting and real activities manipulations. Halabi et al (2019), examine the effect of religiosity, the power-distance, and individualism accompanied by constructed formal institution variables (investor protection, enforcement quality, and equity market development) and a set of other control variables. The major findings tend to real earnings management methods in countries that religious and cultural factors have a significant impact on the management procedures.…”
Section: Issue 7: the Concentration Degree In The Marketmentioning
confidence: 99%
“…Newest studies attempt to investigate qualitative issues such as the religious and cultural aspects associated with accounting and real activities manipulations. Halabi et al (2019), examine the effect of religiosity, the power-distance, and individualism accompanied by constructed formal institution variables (investor protection, enforcement quality, and equity market development) and a set of other control variables. The major findings tend to real earnings management methods in countries that religious and cultural factors have a significant impact on the management procedures.…”
Section: Issue 7: the Concentration Degree In The Marketmentioning
confidence: 99%
“…Nilai absolut akrual yang tingging lebih sering terjadi pada perusahaan dengan tingkat pertumbuhan yang tinggi. Perushaan yang memiliki pertumbuhan yang tinggi mempunyai insentif untuk mempertahankan tingkat pertumbuhannya yang tinggi dengan melakukan manajemen laba (Halabi, Alshehabi, and Zakaria 2019). Dalam penelitin ini pertumbuhan perusahaan diukur dengan price book value (PBV).…”
Section: Pertumbuhan Perusahaan (Growth)unclassified
“…Literature also suggests two categories related to earnings management: Accruals-based Earnings Management or AEM and REM (Al-Haddad and Whittington, 2019;Gutiérrez and Rodríguez, 2019). While the former relates to accounting practices, the latter to the company's operating practices (Gutiérrez and Rodríguez, 2019;Halabi et al, 2019). Malikov et al (2018) found three earnings management tools in literature, Accruals-based Earnings Management, REM, and classification shifting.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%